ARTIFICIAL INTELLIGENCE IN THE RECRUITMENT AND SELECTION OF EMPLOYEES WORLDWIDE VS. ROMANIA - Alina Mihaela FRĂTICĂ-DRAGOMIR (GUȘE) (Annals of the University of Oradea: Economic Science)
In this era of globalization, an organization must thrive and survive in the global economy. Every employer of the organization or manager of public institutions must promote and practice the recruitment and selection process in a way as close to perfection as possible. The success of the organization or a public institution itself depends on qualified employees and is directly related to the performance of the organization. A proper recruitment and selection process is the lifeblood, like capital, of any public organization or institution. The eminence of human resources depends on the effectiveness of real recruitment and selection procedures. The purpose of recruitment and selection is to bring to the surface qualified candidates for the organization. The main goal of all employers is to select qualified candidates from the alternative group of qualified candidates for a particular job. All activities of the recruitment and selection process are carried out by the human resources department of an organization. These processes vary from one organization to another. Traditional sources are employee recommendations, transfers, promotions, presentations, and advertisements. However, the recruitment process differs from organization to organization. In the modern economy, the recruitment process is changing drastically with the advent of social networks. The second stage of the workforce planning process is selection. It is the process of choosing the most suitable candidate who corresponds to the knowledge, skills, abilities and requirements of the job. In the case study, we make critical assessments on how to select the person suitable for the given position and for the development of the organization or public institution. In Romania it is necessary to develop new methods using technology through artificial intelligence